2007
DOI: 10.1063/1.2715561
|View full text |Cite
|
Sign up to set email alerts
|

Chemical origin of blue- and redshifted hydrogen bonds: Intramolecular hyperconjugation and its coupling with intermolecular hyperconjugation

Abstract: Upon formation of a H bond Y...H-XZ, intramolecular hyperconjugation n(Z)-->sigma*(X-H) of the proton donor plays a key role in red- and blueshift characters of H bonds and must be introduced in the concepts of hyperconjugation and rehybridization. Intermolecular hyperconjugation transfers electron density from Y to sigma*(X-H) and causes elongation and stretch frequency redshift of the X-H bond; intramolecular hyperconjugation couples with intermolecular hyperconjugation and can adjust electron density in sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 17 publications
1
41
1
Order By: Relevance
“…Figure 5 illustrates selected orbitals involved in the above-mentioned two-step mechanism. It must be mentioned that a similar effect has been demonstrated for the CHF 3 molecule hydrogen-bonded to proton acceptor of medium strength [75]. In the isolated CHF 3 molecule, the intramolecular hyperconjugation energy occurring from the three F atoms to the σ*(CH) bond is equal to 26.40 kcal mol −1 .…”
Section: Nbo Analysissupporting
confidence: 64%
“…Figure 5 illustrates selected orbitals involved in the above-mentioned two-step mechanism. It must be mentioned that a similar effect has been demonstrated for the CHF 3 molecule hydrogen-bonded to proton acceptor of medium strength [75]. In the isolated CHF 3 molecule, the intramolecular hyperconjugation energy occurring from the three F atoms to the σ*(CH) bond is equal to 26.40 kcal mol −1 .…”
Section: Nbo Analysissupporting
confidence: 64%
“…Many research groups had recently reported several theoretical studies showing the weak X-H/Y hydrogen bond formation giving rise to an unexpected blue shift in the X-H stretching frequency, shortening the X-H bond. [67][68][69][70] This fact was valid only for weak hydrogen bonds, in which rehybridization factor (responsible for shortening of the X-H bond) was more pronounced than hyperconjugation-induced X-H bond lengthening. These studies also gave experimental evidence of blue-shifted hydrogen bonds in matrix-isolation and low temperatures.…”
mentioning
confidence: 99%
“…7 This unique phenomenon occurs only in weak hydrogen bonds, in which the re-hybridization factor responsible for the shortened X-H bond is more pronounced than hyper-conjugation, resulting in the lengthening of the X-H bond. 10 Indeed, blueshifted # as (C-F) and # s (C-F) bands of PSi5 were also found in cast film, here resulting from weak Si/FC interactions. 13 The unusual blueshifted # as (C-F) and # s (C-F) bands from the PSi1a copolymer gel implied the possibility of Si/FC interactions.…”
Section: F{mentioning
confidence: 99%
“…[5][6][7][8][9][10] Although weak noncovalent interactions are generally unstable, they are essential for constructing adaptable and hierarchical structures in nature. Self-assembly, smart functions, and conformation stabilization in these structures may result from the combination of multiple types of weak noncovalent interactions in small molecules, synthetic polymers, and biopolymers.…”
mentioning
confidence: 99%